Mobilizing Metaphors in Criminological Analysis: a Case Study of Emotions in the Penal Voluntary Sector - Quinn, Kaitlyn (The British journal of criminology, 2024)
Metaphors pervade media and political constructions of crime and justice, provoking responses and shaping actions. Scholarship in adjacent disciplines illustrates that emotion-metaphors offer unique insight into emotional and interpretive processes, valuably illuminating sense-making, problem solving and action. Yet, metaphors are rarely analysed within criminology, leaving an important opportunity for theorizing emotions and their implications largely unrealized. We explore the analytical and theoretical potential of emotion-metaphors for criminology, using empirical research conducted in the penal voluntary sectors of England and Scotland. Drawing on focus groups with volunteers and paid staff, we analyse the metaphors that non-profit practitioners mobilized to convey how their work felt: (1) absurd and unstable, (2) vulnerable and constrained, (3) devalued and discarded and (4) risky and all-consuming.